THE EFFECT OF GREEN MARKETING MIX ON PURCHASE DECISIONS FOR TUPPERWARE PRODUCTS IN EAST ACEH DISTRICT. - Said Abdillah; Rahmaniar; Chalirafi; Khairina AR (RADJA PUBLIKA, 2025)
This study aims to determine the influence of the green marketing mix on purchasing decisions for Tupperware products in East Aceh Regency. The data used in this study are primary data. The sampling technique used purposive sampling with a sample size of 140.The conclusion of the theory above is fulfilled. The method used to analyze the relationship between the independent variable and the dependent variable is the multiple linear regression method. The results of the study indicate that partially Green product has a positive and significant effect on the decision to purchase Tupperware products. Green price has a positive and significant effect on the decision to purchase products. Green place has a positive and significant effect on the decision to purchase Tupperware products. Green promotion has a positive and significant effect on the decision to purchase Tupperware products.